Orthodox Judaism through the Eyes of Women Characters in Rebecca Goldstein’s Mazel - Monika Tekielová (American and British Studies Annual, 2013)
This paper deals with the novel by Rebecca Goldstein Mazel, the main focus of which rests on four generations of Jewish women and their relationship with Orthodox Judaism. Two worlds are put in contrast: that of a shtetl in prewar Eastern Europe and that of a modern Orthodox Jewish community in North America. Sasha Saunders, who was born in the shtetl and has relocated to New York, has abandoned her religion and cannot understand that her granddaughter has decided to settle down in a Modern Orthodox community in New Jersey and thus to go back to the “old ways.”